PEMETAAN PERUBAHAN PENGGUNAAN LAHAN PERMUKIMAN DAN POLA PERMUKIMAN DI KOTA PARIAMAN TAHUN 2010, 2015 DAN 2020 - Susilo, Arga (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Population growth and development activities in various fields in the city of Pariaman are increasingly demanding the availability of land, especially residential land. Meanwhile, land availability is limited. This land imbalance results in changes in land use which will then form a pattern of distribution of settlements so that information about changes in land use and settlement patterns is needed. This study aims to (1) determine changes in residential land use in Pariaman City in 2010, 2015 and 2020 (2) Find out the distribution pattern of settlements in Pariaman City in 2010, 2015 and 2020. This research method uses remote sensing techniques and geographic information systems with interpretation of land use on Landsat 7 and Landsat 8 images classified using supervised classification and then analyzed using nearest neighbor analysis to determine the distribution pattern of settlements in Pariaman city. Based on the results of processing and analysis, it was found that the residential area of Pariaman City in 2010 was 860.22 ha, in 2015 it was 1415.09 ha and in 2020 it was 1638.64 ha. The pattern of distribution of settlements in 2010 has 2 patterns, namely clustered and random with a clustered area of 443.74 ha and a random area of 416.16 ha, in 2015 it was clustered in an area of 825.75 ha and a random area of 589.72 ha, in 2020 it was clustered in an area of 954,91 ha and random area of 673.59 ha